Relationships of circulating pregnanolone isomers and their polar conjugates to the status of sex, menstrual cycle, and pregnancy - Kancheva, Radmila; Hill, Martin; Cibula, David; Vceláková, Helena; Kancheva, Lyudmila; Vrbíková, Jana; Fait, Tomás; Parízek, Antonín; Stárka, Luboslav (The Journal of endocrinology, 2007)
Pregnanolone isomers (PIs) and their polar conjugates (PICs) modulate ionotropic receptors such as gamma-aminobutyric acid or pregnane X receptors. Besides, brain synthesis, PI penetrates the blood-brain barrier. We evaluated the physiological importance of PI respecting the status of sex, menstrual cycle, and pregnancy. Accordingly, circulating levels of allopregnanolone (P3alpha 5alpha ), isopregnanolone (P3beta 5alpha ), pregnanolone (P3alpha 5beta ), epipregnanolone (P3beta 5beta ), their polar conjugates, and related steroids were measured in 15 men (M), 15 women in the follicular phase (F), 16 women in the luteal phase (L), and 30 women in the 36th week of gestation (P) using GC-MS. The steroid levels were similar in M and F, increased about thrice in L and escalated in P (38-410 times compared with F). The PICs were prevalent over the PIs (16-150 times). Higher ratios of 5alpha-PIC to 5alpha-PI found in P indicate the more intensive conjugation of 5alpha-PI during pregnancy. This mechanism probably provides for the elimination of neuroinhibitory P3alpha 5alpha in the maternal compartment. Additionally, our result points to a limited sulfation capacity for neuroinhibitory P3alpha 5beta in P. In contrast to the situation in M, F, and L where the P3alpha 5beta C is the most abundant PIC, and P3alpha 5beta is present in minor quantities compared with the P3alpha 5alpha, P3alpha 5beta may acquire physiological importance during pregnancy, contributing to the sustaining thereof. On the other hand, the declining formation of P3alpha 5beta may participate in the initiation of parturition, given the relative abundance of the steroid, its potency to suppress the activity of oxytocin-producing cells and its effectiveness in uterine relaxation.
Keywords: Analysis of Variance; dospělí; Female; Adult; ženské pohlaví; Sex; Menstrual Cycle; Adolescent; lidé; těhotenství; Stereoisomerism; stereoizomerie; Luteal Phase; Pregnanolone; Middle Aged; menstruační cyklus; analýza rozptylu; Male; pregnanolon; Follicular Phase; luteální fáze; lidé středního věku; Pregnancy Trimester, Third; mužské pohlaví; třetí trimestr těhotenství; Pregnancy; folikulární fáze; mladiství; pohlaví; Humans